Home-grown and grassroots-based strategies for determining inequality towards policy action: Rwanda's Ubudehe approach in perspective - Chika Ezeanya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Survey-based tools for determining inequality in Africa south of the Sahara have been critiqued for being too expensive, and oftentimes unsuitable to the realities of the region. The need for a reliable alternative for determining wealth distribution, from which data can be generated for policy action, has been a challenge. Rwanda, however, using the Ubudehe community-based practice has been able to determine household inequality across the nation. Data generated through Ubudehe has been used in policy-making, including in the key health and education sectors. Using both primary and secondary methods, the study explores the successes, challenges, and opportunities of Ubudehe-generated inequality data in policy formulation and implementation.
Keywords: O1; O2; O12; O13; 330; Ubudehe; Rwanda; grassroots; home-grown; inequality measurement; African development